(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Chemical peels are useful cosmetic procedures for skin renewal. Their success can be attributed to their simplicity and versatility. Chemical peels are categorized as superficial, medium, or deep based on how far the peeling solution penetrates the skin. The procedure’s outcomes are dependent upon the chemical and its concentration, application technique, duration of contact, skin type, readiness, etc. The degree of peeling affects the patient’s discomfort both during and after the treatment, how quickly they heal, how frequently they may experience side effects, and the outcome. Chemical peel can reduce or improve fine lines and wrinkles, acne scars, uneven skin colouring and skin imperfections.